2016
DOI: 10.1002/er.3620
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of segmented leg for the enhanced performance of segmented thermoelectric generator

Abstract: Summary Thermal analysis of a segmented thermoelectric generator is performed, and the segmented leg configurations maximizing the efficiency and the output power are formulated. The effect of operating conditions such as external load resistance, the temperatures of hot and cold junctions, on the device performance is studied. The segmented thermoelectric generator has the leg configuration consisting of the combination of modified lead telluride and modified bismuth telluride. The segmented thermoelectric ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The advantages of WHR include a decrease in the consumption costs, equipment sizes, pollution, and auxiliary energy consumption. Though a lot of WHR systems are available, the thermoelectric generator (TEG) is a green energy source and a promising energy harvesting device, which is widely used in automotive, military, and battery charging applications.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of WHR include a decrease in the consumption costs, equipment sizes, pollution, and auxiliary energy consumption. Though a lot of WHR systems are available, the thermoelectric generator (TEG) is a green energy source and a promising energy harvesting device, which is widely used in automotive, military, and battery charging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric generators (TEGs) are potential alternative green energy sources [1][2][3][4] which are growing popularly to overcome the issues of environmental pollution and global energy crisis. Thermoelectric generators (TEGs) are potential alternative green energy sources [1][2][3][4] which are growing popularly to overcome the issues of environmental pollution and global energy crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid development and the increasing energy demand for comfort require the development of more alternative energy sources. Thermoelectric generators (TEGs) are potential alternative green energy sources [1][2][3][4] which are growing popularly to overcome the issues of environmental pollution and global energy crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Sahin and Yilbas analysed the performance of thermoelectric generator and influence of thermoelectric geometry on the device performance theoretically and concluded that the shape parameter of the device has favourable effect on efficiency and reverse effect on the power output. Ali and Yilbas carried out the thermal analysis of the segmented thermoelectric generator and compared the power output and efficiency of segmented TEG with the conventional configuration having single material for the same operating conditions. Kaushik and Manikandan determined the energy and exergy efficiency of annular thermoelectric generator by taking Thomson effect into account.…”
Section: Introductionmentioning
confidence: 99%